(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To identify behavioral factors associated with obesity among lower secondary school students in Tien Giang province. Method: A case-control study design was employed, involving 1440 students (720 obese and 720 with normal weight), with data collected on anthropometric indices, dietary habits, physical activity, and lifestyle factors. Univariate analyses and multivariate logistic regression were used to identify factors associated with obesity. Results: Several behaviors significantly associated with increased obesity risk, including inadequate breakfast consumption (< 5 times/week), dining out ≥ 3 times/week, eating quickly without thorough chewing, consumption of sugar-sweetened beverages, use of electronic devices during meals, and sleeping less than 8 hours per night. Multivariate analysis identified 4 independent risk factors: inadequate breakfast (OR = 3.18), frequent dining out (OR = 2.24), insufficient sleep (OR = 2.17), and rapid eating (OR = 1.67). Conclution: These findings highlight the complex interplay between dietary habits, lifestyle behaviors, and environmental influences in the development of school-age obesity, suggesting targeted avenues for intervention. Effective obesity prevention strategies require a multidimensional approach involving families, schools, and communities to foster healthy lifestyles among adolescents.